Reviewing Gadamer's Hermeneutics in Communication Studies - Bayujati Prakoso (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
Hermeneutics is a theory and method of interpretation. Originally, Hermeneutics was used to interpret scripture, such as the Bible. Now, as time goes by, Hermeneutics was not only used to interpret the scriptures but other general texts. It is in the study of communication relating to the message (meaning), allowing relevance to Hermeneutics' emergence as a message interpretation approach. This is because a text is a medium to convey a communication message. This article aims to explain that there is a potential for Hermeneutics in contemporary communication studies. The focus of this article review is Gadamer's Hermeneutics. It is an effort to improve communication studies' knowledge, besides, to study in Indonesia on Content Analysis, Framing Analysis, and Critical Discourse Analysis (CDA). This article found that the study of hermeneutics studies has not been widely used to analyze communication issues & contemporary media. In this context, Hermeneutics requires an understanding of an interpretive dialogue that does not end up in communication (messages). Then, Hermeneutics can be used to gain a Hermeneutics understanding and to interpret texts, such as magazines, books, poems, speeches, songs, movies, reports, documents/articles, or news texts in print or online. This will be a starting point of hermeneutics to understand the reality of communication phenomena